Study of Cultural Dilemma and Internal System of Chinese Learning for International Students in Zhengzhou University, China - Ghulam Jilani; Guangqin Yang (International Journal of Sociology of Education, 2022)
This study focuses on international students’ satisfaction on-campus cultural environment, living, learning experience about the quality of education and available facilities. A questionnaire-based cross-sectional systemic survey where 119 foreign students were targeted for data collection using the strategy of non-probability convenience sampling. For data processing, SPSS v 22.0 was adopted and P≤0.05 was considered statically significant. To explore the relationship between variables, the Kruskal-Wallis H and Mann-Whitney U tests were carried out. The results show a high level of foreign students’ satisfaction with adequate accommodation, the influence of Chinese culture, and the quality of education. This study evaluated that the overall better level of satisfaction in culture, living, the standard of education, learning system, cost of accommodation, and sports